A niche perspective on the range expansion of symbionts. (5th December 2019) - Mestre, Alexandre; Poulin, Robert; Hortal, Joaquín
ABSTRACT: Range expansion results from complex eco‐evolutionary processes where range dynamics and niche shifts interact in a novel physical space and/or environment, with scale playing a major role. Obligate symbionts (i.e. organisms permanently living on hosts) differ from free‐living organisms in that they depend on strong biotic interactions with their hosts which alter their niche and spatial dynamics. A symbiotic lifestyle modifies organism–environment relationships across levels of organisation, from individuals to geographical ranges. These changes influence how symbionts experience colonisation and, by extension, range expansion. Here, we investigate the potential implications of a symbiotic lifestyle on range expansion capacity. We present a unified conceptual overview on range expansion of symbionts that integrates concepts grounded in niche and metapopulation theories. Overall, we explain how niche‐driven and dispersal‐driven processes govern symbiont range dynamics through their interaction across scales, from host switching to geographical range shifts. First, we describe a background framework for range dynamics based on metapopulation concepts applied to symbiont organisation levels. Then, we integrate metapopulation processes operating in the physical space with niche dynamics grounded in the environmental arena. For this purpose, we provide a definition of the biotope (i.e. living place) specific to symbionts as a hinge concept to link the physical and environmental spaces, wherein the biotope unit is a metapopulation patch (either a host individual or a land fragment). Further, we highlight the dual nature of the symbionts' niche, which is characterised by both host traits and the external environment, and define proper conceptual variants to provide a meaningful unification of niche, biotope and symbiont organisation levels. We also explore variation across systems in the relative relevance of both external environment and host traits to the symbiont's niche and their potential implications on range expansion. We describe in detail the potential mechanisms by which hosts, through their function as biotopes, could influence how some symbionts expand their range – depending on the life history and traits of both associates. From the spatial point of view, hosts can extend symbiont dispersal range via host‐mediated dispersal, although the requirement for among‐host dispersal can challenge symbiont range expansion. From the niche point of view, homeostatic properties of host bodies may allow symbiont populations to become insensitive to off‐host environmental gradients during host‐mediated dispersal. These two potential benefits of the symbiont–host interaction can enhance symbiont range expansion capacity. On the other hand, the central role of hosts governing the symbiont niche makes symbionts strongly dependent on the availability of suitable hosts. Thus, environmental, dispersal and biotic barriers faced by suitable hosts apply also to the symbiont, unless eventual opportunities for host switching allow the symbiont to expand its repertoire of suitable hosts (thus expanding its fundamental niche). Finally, symbionts can also improve their range expansion capacity through their impacts on hosts, via protecting their affiliated hosts from environmental harshness through biotic facilitation.